2020
DOI: 10.1093/carcin/bgaa113
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor Sp1 is upregulated by PKCι to drive the expression of YAP1 during pancreatic carcinogenesis

Abstract: Recently, we identified that the atypical protein kinase C isoform ι (PKCι) enhances the expression of YAP1 to promote the tumorigenesis of pancreatic adenocarcinoma harboring mutant KRAS (mu-KRAS). To advance our understanding about underlying mechanisms, we analyze the transcription of YAP1 in pancreatic cancer cells and reveal that transcription factor Specificity Protein 1 (Sp1) is upregulated by PKCι and subsequently binds to multiple sites in YAP1 promoter to drive the transactivation of YAP1 in pancreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…The oncogenic role of PRKCI-encoding protein PKC iota has been well established, recent studies in PC suggested that mutated KRAS can elevate and activate PKC iota to disable growth-inhibitory Hippo signaling and promote Yes-associated protein1 (YAP-1) translocation into nucleus, and thus maintain PC cells growth (Wang et al 2020 ). Also, PKC iota upregulates transcription factor specificity protein 1 to promote transactivation of YAP-1 and induce tumorigenesis (Yang et al 2021 ). In turn, the produced YAP-1 can be recruited by PKC iota to increase PD-L1 expression, resulting in immune evasion under the microenvironment of PC (Zhang et al 2021c ).…”
Section: Discussionmentioning
confidence: 99%
“…The oncogenic role of PRKCI-encoding protein PKC iota has been well established, recent studies in PC suggested that mutated KRAS can elevate and activate PKC iota to disable growth-inhibitory Hippo signaling and promote Yes-associated protein1 (YAP-1) translocation into nucleus, and thus maintain PC cells growth (Wang et al 2020 ). Also, PKC iota upregulates transcription factor specificity protein 1 to promote transactivation of YAP-1 and induce tumorigenesis (Yang et al 2021 ). In turn, the produced YAP-1 can be recruited by PKC iota to increase PD-L1 expression, resulting in immune evasion under the microenvironment of PC (Zhang et al 2021c ).…”
Section: Discussionmentioning
confidence: 99%
“…These changes promote the growth of pancreatic cancer [ 248 ]. Inhibition of PKCι alone [ 249 ] or in combination with other inhibitors (e.g., specificity protein 1 (Sp1) inhibitor) [ 250 ] reduced cell growth and metastasis and induced apoptosis in pancreatic cancer cells. These studies suggest that PKCι can be a promising therapeutic target for pancreatic cancer.…”
Section: Pkc Isozymes As Prognostic Biomarkers or Therapeutic Targets...mentioning
confidence: 99%
“…The expression and function of proliferative Yes-associated protein (YAP1) have shown to be upregulated in KRAS mutated PDAC through the atypical protein kinase C isoform ι (PKCι), leading to the progression of PDAC, reprogramming of microenvironment, and immune invasion of PDAC [ 98 ]. PKCι has been shown to upregulate another important protein called Specificity protein 1 (Sp1).…”
Section: Kras Mutation In Patients With Diabetes Mellitusmentioning
confidence: 99%
“…This protein is the first identified member of the Sp/XKLF (specificity protein/Krüppel-like factor) family of transcription factors shown to modulate apoptosis, differentiation, angiogenesis, and growth of many different cell types [ 99 ]. It has been reported that upregulated Sp1via PKC1 can bind to multiple sites of YAP1 promoter driving its transcription, which ultimately leads to upregulation of PDl-1 and thus the proliferation of PDAC as well as cytotoxic immune response resistance [ 98 ]. The induction of apoptosis and reversion of the immunosuppression of pancreatic cancer cells was accomplished through the combination of PKCι and Sp1 inhibitors at sub-toxic doses.…”
Section: Kras Mutation In Patients With Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation